2010
DOI: 10.1210/jc.2009-1151
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hemoglobin A1c Greater Than 6.5% and 7.0% among Hospitalized Patients without Known Diagnosis of Diabetes at an Urban Inner City Hospital

Abstract: In communities with high prevalence of diabetes, a large percentage of patients without a diagnosis of diabetes who are admitted as in-patients have HbA1c of at least 6.5% and 7.0%. Hospital-based HbA1c testing might identify patients for whom further testing is indicated to make the diagnosis of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 14 publications
0
26
1
3
Order By: Relevance
“…28 Measurement of HbA1c in patients with hyperglycemia during hospitalization provides the opportunity to differentiate patients with stress hyperglycemia from those with diabetes who were previously undiagnosed. 29 The Endocrine Society guidelines indicate that patients with hyperglycemia and HbA1C of 6.5% or higher can be identified as having diabetes. 30 …”
Section: Introductionmentioning
confidence: 99%
“…28 Measurement of HbA1c in patients with hyperglycemia during hospitalization provides the opportunity to differentiate patients with stress hyperglycemia from those with diabetes who were previously undiagnosed. 29 The Endocrine Society guidelines indicate that patients with hyperglycemia and HbA1C of 6.5% or higher can be identified as having diabetes. 30 …”
Section: Introductionmentioning
confidence: 99%
“…[2] More recently, the use of glycated hemoglobin (HbA1c) has been recommended over oral glucose tolerance test as the preferred diagnostic testing in hospitalized patients with hyperglycemia. [3] Measurement of an HbA1c during periods of hospitalization provides the opportunity to differentiate patients with stress hyperglycemia from those with diabetes who were previously undiagnosed. [4]…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 25% of hospitalized patients carry the diagnosis of diabetes, and potentially up to another 18% to 25% of patients have undiagnosed type 2 diabetes [15, 16•, 17]. The RABBIT 2 (Randomized Study of Basal-Bolus Insulin Therapy in the Inpatient Management of Patients with Type 2 Diabetes) trial, published in 2007, and its surgical counterpart, published in 2011, have demonstrated the benefits of basal-bolus insulin compared with sliding scale alone for glycemic control in general medicine and surgical type 2 diabetes patients, respectively.…”
Section: Introductionmentioning
confidence: 99%